1976
DOI: 10.1002/cpt1976194416
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the pharmacokinetics of acebutolol

Abstract: Using a balance, randomized, crossover design, single intravenous (1 mg/kg) or oral (3 X 100 mg) doses of acebutolol were administered at weekly intervals to 6 healthy volunteers. For each subject venous blood samples and timed urine collections were obtained after each treatment. Plasma and urinary acebutolol levels were measured by a spectrophotometric method that measures acebutolol and its N-acetyl metabolite (which has equivalent cardiac activity). Using a computer program, various pharmacokinetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…The test set of five drugs used in the multi-functional scaling approach to evaluate the resulting design parameters for multi-MPS platform I included: acetaminophen 45 , clozapine 46 , imipramine 47 , oxazepam 48 and sildenafil 49 ; for multi-MPS platform II: acebutolol 50 , alprazolam 51 , indomethacin 52 , ketoprofen 53 and nadolol 54 . References indicate source of time-concentration profiles and administered dose.…”
Section: Methodsmentioning
confidence: 99%
“…The test set of five drugs used in the multi-functional scaling approach to evaluate the resulting design parameters for multi-MPS platform I included: acetaminophen 45 , clozapine 46 , imipramine 47 , oxazepam 48 and sildenafil 49 ; for multi-MPS platform II: acebutolol 50 , alprazolam 51 , indomethacin 52 , ketoprofen 53 and nadolol 54 . References indicate source of time-concentration profiles and administered dose.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have provided data on the plasma concentration of acebutolol (Gibbons, Lant, Ashford, Collins & Pinder, 1976; Kaye, Kumana, Leighton, Hamer & Turner, 1976;Kumana, Leighton, Kaye, Turner & Hamer, 1975; Kaye & Long, 1976;Kaye & Dufton, 1976;Roux, Flouvat & Delaveau, 1975;Collins, 1975). These studies, however, use non-specific methods of assay which measure acebutolol and potential metabolites as a single species.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Treatment with the ,B-adrenoceptor-blocking drug acebutolol is effective for a variety of cardiac conditions (Lewis, Bakst, Kitchiner & Gotsman, 1973;Ricks, Harrison, Bell & Winkle, 1976;Lewis, Mitna & Gotsman, 1974;Biron, Proulx, Lapointe, Nadeau & Tremblay, 1975). Several recent studies have provided data on the plasma concentration of acebutolol (Gibbons, Lant, Ashford, Collins & Pinder, 1976; Kaye, Kumana, Leighton, Hamer & Turner, 1976; Kumana, Leighton, Kaye, Turner & Hamer, 1975;Kaye & Long, 1976;Kaye & Dufton, 1976;Roux, Flouvat & Delaveau, 1975;Collins, 1975). These studies, however, use non-specific methods of assay which measure acebutolol and potential metabolites as a single species.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…For example theoretical S/P ratio for propranolol can change in a 30-fold range when saliva pH varies in the physiologic range from 6.5 to 8. Recently, Kaye et al (1977) reported a S/P ratio of0.815 for acebutolol but on the one hand no saliva pH values were given and on the other hand the analytical method used (Kaye, Kumana, Leighton, Hamer & Turner, 1976) was not specific, detecting not only acebutolol but also its metabolites, including the acetyl analogue.…”
Section: Acebutolol Saliva Excretionmentioning
confidence: 99%